2011
DOI: 10.1039/c0ee00213e
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency nanocomposite sorbents for CO2 capture based on amine-functionalized mesoporous capsules

Abstract: Increases in atmospheric carbon dioxide gas have been linked to increasing use of fossil fuels over the past century. Post-combustion capture has the greatest near-term potential for reducing CO 2 emissions. Solid sorbents provide a promising alternative to conventional amine solutions for CO 2 capture. However, practical CO 2 capture applications have been impeded primarily by limited sorbent capacity and recyclability. Here we present a novel CO 2 capture platform based on oligomeric amines supported on spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
422
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 474 publications
(446 citation statements)
references
References 48 publications
19
422
2
3
Order By: Relevance
“…At high temperature, the high CO 2 adsorption capacity is possibly due to the high diffusion rate of CO 2 into bulklike PEI and the increasing reaction rate of CO 2 with PEI. The similar observation was also reported by HeydariGorji and Sayari (2011) and Qi et al (2011). Song's group further studied the effect of moisture on CO 2 capture using the PEI/MCM-41 and showed that the CO 2 adsorption capacity was increased from 2.03 mmol/g for an anhydrous flow containing 15% of CO 2 to 2.84 mmol/g for a flow containing 10% of moisture and 13% of CO 2 .…”
Section: Fig 3 (Continued)supporting
confidence: 64%
“…At high temperature, the high CO 2 adsorption capacity is possibly due to the high diffusion rate of CO 2 into bulklike PEI and the increasing reaction rate of CO 2 with PEI. The similar observation was also reported by HeydariGorji and Sayari (2011) and Qi et al (2011). Song's group further studied the effect of moisture on CO 2 capture using the PEI/MCM-41 and showed that the CO 2 adsorption capacity was increased from 2.03 mmol/g for an anhydrous flow containing 15% of CO 2 to 2.84 mmol/g for a flow containing 10% of moisture and 13% of CO 2 .…”
Section: Fig 3 (Continued)supporting
confidence: 64%
“…% (75°C and 1 bar) with fast adsorption kinetics was observed (Qi et al, 2012). Similar capacities were achieved from the same group by using mesoporous SiO 2 capsules as a support (Qi et al, 2011), the measured pore volume of the capsules was not high, however, the hollow cores provided abundant space for the accommodation of amines, leading to the exceptionally high adsorption capacities.…”
Section: Effect Of Supportsupporting
confidence: 60%
“…Basically, owing to the higher concentration of amine groups, larger amounts of primary amine, and lower viscosity, higher capacities can be obtained by using TEPA as compared with that of PEIs. However, the cyclic stability of using TEPA is questionable due to its lower thermal stability which led to amine loss during desorption at elevated temperatures (Chen et al, 2009;Liu et al, 2010;Qi et al, 2011). A similar theory can be applied to linear PEI as well.…”
Section: Effect Of Aminesmentioning
confidence: 99%
“…3 Most of advanced amine-supported sorbents up to now have been synthesized by the immobilization of amines into mesoporous supports via one of the following strategies: post-grafting, wet impregnation and cocondensation of aminosilanes and tetraalkoxysilanes. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although sorbents with relatively high amine loadings can be achieved, post-grafting and wet impregnation involve multi-step synthesis in which the supporting materials are separately prepared. In addition, the increase of amine content of the sorbents comes usually at the expense of surface area and pore volume available for CO 2 capture ultimately compromising the performance of the sorbents.…”
mentioning
confidence: 99%
“…The two-stage adsorption behavior is typical of other amine-based solid sorbents 3, 4, 15 and has been attributed to CO 2 diffusion resistance in the sorbents. [3][4][5]16 The adsorption kinetics of the sorbent was also investigated gravimetrically in simulated flue gas (prehumified 10% CO 2 ) at 25 o C under ambient pressure. The activated sorbent was first equilibrated in the pre-humified N 2 at 25 o C for 4 h. A weight gain of ~ 8 wt % was attributed to the adsorption of moisture (see Fig.…”
mentioning
confidence: 99%